Chemical and mineralogical compositions of two grains recovered from asteroid Itokawa. (12th February 2015) - Ebihara, M.; Shirai, N.; Sekimoto, S.; Nakamura, T.; Tsuchiyama, A.; Matsuno, J.; Matsumoto, T.; Tanaka, M.; Abe, M.; Fujimura, A.; Ishibashi, Y.; Karouji, Y.; et al.
Abstract Two silicate grains (RB‐QD04‐0049 and RA‐QD02‐0064, whose estimated masses are 0.050 μg and 0.048 μg, respectively) recovered from the asteroid Itokawa by the Hayabusa spacecraft were studied for their mineralogical characteristics by synchrotron X‐ray diffraction and synchrotron X‐ray microtomography and further analyzed for their bulk chemical compositions by instrumental neutron activation analysis (INAA). According to X‐ray tomography, RB‐QD004‐0049 is composed of olivine, high‐Ca pyroxene, plagioclase, Ca‐phosphate, and troilite, whereas RA‐QD002‐0064 entirely consists of olivine. INAA data are consistent with these mineral compositions except for rare earth elements (REEs). Although the grain RB‐QD004‐0049 contains measurable REEs, which seems to be consistent with the presence of Ca‐phosphate, their abundances are anomalously high. Very low abundance of Co implies less than 0.1 mass% of metals in these two grains by calculation, which is in contrast to the result for the previously analyzed grain RA‐QD02‐0049 (Ebihara et al., 2011). FeO/Sc ratios of the grains fall within the range of those for ordinary chondrite olivines, implying that these grains are extraterrestrial in origin. FeO/MnO ratios also confirm this conclusion and further suggest that the Hayabusa grains analyzed in this study are similar to material found in LL chondrites rather than CK chondrites although olivines from LL and CK chondrites have similar Fa# (molar% of Fe relative to [Fe+Mg] in olivine) (~30) to those of the Hayabusa grains including the two grains analyzed in this study.